2022
DOI: 10.3390/ijerph19031598
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Self-Perceived Quality of Life in Sports Students: A Case Study

Abstract: Adolescence has been considered a crucial stage for the adoption of healthy habits such as physical activity. In addition, numerous research studies have shown that physical activity is a positive factor for health behaviors and quality of life. In this sense, the aim of this study was to examine the relationship between physical activity levels and perceived quality of life in a sample of students studying physical activity and sport. This is a descriptive observational study with a population of physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(64 reference statements)
0
0
0
3
Order By: Relevance
“…Kirschner et al (2021) found a significant positive association between physical activity and self-esteem. Similarly, the study by Gavala-Gonzalez et al (2022) suggests an inverse relationship between participation in physical activity and emotional problems. Jensen et al (2022) also highlighted the positive relationship between positive mental health and the likelihood of meeting the recommended standard for physical activity.…”
Section: Physical Activity Is Positively Associated With Positive Men...mentioning
confidence: 88%
See 1 more Smart Citation
“…Kirschner et al (2021) found a significant positive association between physical activity and self-esteem. Similarly, the study by Gavala-Gonzalez et al (2022) suggests an inverse relationship between participation in physical activity and emotional problems. Jensen et al (2022) also highlighted the positive relationship between positive mental health and the likelihood of meeting the recommended standard for physical activity.…”
Section: Physical Activity Is Positively Associated With Positive Men...mentioning
confidence: 88%
“…Three of the studies investigated the relationship between aspects of positive mental health and school environment (Gashi & Mojsoska-Blazevski, 2016;Krawczynska & Zawierucha, 2018;Warne et al, 2013). Three studies explored the relationship between aspects of positive mental health and physical activity (Gavala-Gonzalez et al, 2022;Jensen et al, 2022;Kirschner et al, 2021). One study explored the relationship between quality of life and sleep duration (Stheneur et al, 2019).…”
Section: Rq 3) What Is the Aim Of The Studies?mentioning
confidence: 99%
“…Por tanto, a los datos que mostraron sujetos con inactividad física durante el confi namiento, presentaron niveles elevados de depresión, ansiedad y estrés, así mismo, su percepción en su salud general, bienestar y calidad de vida comparada con el año previo a la pandemia 38,39,41 .…”
Section: Discussionunclassified
“…A día de hoy se encuentra totalmente sustentado científi camente que la práctica de actividad física en niveles moderados, se ubica dentro de los factores determinantes en la prevención de patologías, físicas y psicológicas, por lo que se reitera que es un elemento clave y sustancial en una vida saludable 4,40 . Así mismo los entes sociales y las sociedades tienen que adaptarse a poblaciones cada vez más numerosas donde debe primar la calidad de vida, siendo la calidad de vida, defi nida por la Organización Mundial de la Salud (OMS) como "la percepción individual de la propia posición en la vida dentro del contexto del sistema cultural y de valores en que se vive y en relación con sus objetivos, esperanzas, normas y preocupaciones" 6,41 .…”
Section: Introductionunclassified
See 1 more Smart Citation